TINGKAT PENDIDIKAN DAN PEKERJAAN ORANG TUA DENGAN PERILAKU HIDUP BERSIH DAN SEHAT PADA ANAK USIA SEKOLAH - Akmalia Nadhifatuz Zahro; Umi Faridah; Indanah Indanah (Jurnal Keperawatan dan Kesehatan, 2026)
Background: Clean and Healthy Living Behavior (CHLB) is a behavior based on personal awareness to maintain and improve health, enabling individuals and families to protect themselves and actively participate in social life. Family-related factors, such as parents’ education level and occupation, are assumed to influence the development of health behaviors in school-aged children. Objective: This study aimed to analyze the relationship between parents’ education level and occupation and clean and healthy living behavior among school-aged children. Methods: This study employed a quantitative method with an analytic observational cross-sectional design. A total of 144 respondents were selected using stratified random sampling. Data were collected using questionnaires measuring parents’ education level, occupation, and children’s clean and healthy living behavior. Univariate analysis was used to describe respondent characteristics, while bivariate analysis using the chi-square test examined the relationships between variables. Results: The results showed that most parents had a basic level of education (43.1%) and worked in the formal sector (62.5%). Meanwhile, 56.9% of children demonstrated good clean and healthy living behavior. The chi-square test indicated no significant relationship between parents’ education level and children’s clean and healthy living behavior (p=0.870), as well as no relationship between parents’ occupation and children’s clean and healthy living behavior (p=0.543). Conclusion: Parents’ education level and occupation are not significantly associated with clean and healthy living behavior among school-aged children.